Valorization of peanut shells through biochar production using slow and fast pyrolysis and its detailed physicochemical characterization - Sawargaonkar, Gajanan; Pasumarthi, Rajesh; Kale, Santosh; Choudhari, Pushpajeet; Rakesh, S.; Mutnuri, Srikanth; Singh, Ajay; Sudini, Harikishan; Ramaraju, Manasa; Singh, Ramesh; Padhee, Arabinda Kumar; Jat, Mangi Lal (Frontiers in Sustainability, 2024)
Valorization of peanut shells has recently gained prominence in the context of thermally converting agricultural waste into biochar, a carbon-rich byproduct with significant potential as a soil amendment. The present study delves into understanding the influence of slow (450 o C and 500 o C ) and fast (550 o C and 600 o C) pyrolysis temperatures with a resident time of 60 and 30 minutes, respectively, on the physico-chemical properties of peanut shell biochar produced in a low-cost kiln. The Scanning Electron Microscopy analysis revealed that increased pyrolysis temperature increased porosity and surface roughness with crystalline deposits.Thermogravimetric analysis showed that increased temperatures contributed to enhanced thermal stability but reduced biochar yield. Pyrolysis temperatures of 450, 500, 550, and 600 o C exhibited 32. 19, 29.13, 21.8, and 19.43 percent conversion efficiency with organic carbon content of 11.57, 6.48, 8.64, and 7.76 percent, respectively. The intensities of functional groups (C-H and C-O) declined, whereas the intensity of C=C and stable carbon content increased with the rise in temperatures. The concentrations of heavy metals in all biochar samples were below permissible limits outlined by international biochar initiatives. The study concluded that slow pyrolysis at 450 o C for 60 minutes resident time is an ideal pyrolytic condition for producing peanut shell biochar in terms of qualitative and quantitative characteristics.